Letter (copy) : Developments in Spain - Citrine, Walter, 1887-1983
012b-0019-001 Secretary's WMC/FC/EK/1496. 21st August, 1939. The Secretary to the Delegation, The Basque Delegation, 14, Eccleston Square, London S.W.1. Dear Sir, DEVELOPMENTS IN SPAIN. I desire to thank you for your letter of the 18th instant forwarding an analysis of General Franco's recent official declarations and speeches on policy. We are very pleased to have this. Yours faithfully, General Secretary. 292/946/12b/19